Soil microbial biomass in relation to fine root in Kiteni hill Sal forest of Ilam, eastern Nepal - Bhattarai, Krishna Prasad; Mandal, Tej Narayan (Nepalese Journal of Biosciences, 2013)
Soil microbial biomass in relation to fine root was studied in Kiteni hill Sal (Shorea robusta) forest of Ilam during summer season. The forest had sandy loam type of soil texture. Organic carbon was higher in 0-15 cm depth (2.09%) than in 15-30 cm depth (1.53%). Total nitrogen of 0- 15 cm depth was 0.173% and in 15-30 cm depth was 0.124%. Soil microbial biomass of carbon of Kiteni hill sal forest was (445.14 ?g g-1) and microbial biomass of nitrogen was (49.07 ?g g-1). Fine root biomass of this forest was 2.34 t ha-1 (<2 mm diameter) and 0.93 t ha-1 (2-5 mm diameter) in 0-15 cm depth and 0.73 t ha-1 (<2 mm diameter) and 0.46 t ha-1 (2-5 mm diameter) in 15-30 cm depth. Organic carbon, total nitrogen, soil microbial biomass carbon and nitrogen of upper layer soil were negatively correlated with fine root biomass of forest. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7493 Nepalese Journal of Biosciences 2 : 80-87 (2012)